The issue of speculative atheism in Pierre Bayle - Primo, Marcelo de Sant’Anna Alves (2014)
When Bayle reflects on the possibility of a speculative atheism, he argues accurately about shows that atheism can make a contribution to several theoretical discussions of order, as the question of free will, providence and evil, for example. If the philosopher Carla pronounced in favor of speculative atheism, he goes further and asserts a natural morality, which, based on common principles to all men, paves solidity and give its fundamental thesis from the Pensées diverses sur la comète: the association between atheism and virtue. Thus, Bayle explains and analyzes the various arguments and points of view regarding the status of speculative philosophical atheism.